Dynamic changes of the EMT spectrum between circulating tumor cells and the tumor microenvironment in human papillomavirus-positive head and neck squamous cell carcinoma. (February 2023) - Ida, Shota; Takahashi, Hideyuki; Tada, Hiroe; Mito, Ikko; Matsuyama, Toshiyuki; Chikamatsu, Kazuaki
Highlights: Differences in circulating tumor cells between HPV-positive and -negative HNSCC. Changes of EMT-related gene expression in circulating tumor cells. Clinical significance of SNAI1 expression in circulating tumor cells. Abstract: Objectives: Human papillomavirus (HPV)-positive head and neck squamous cell carcinoma (HNSCC) differs in terms of cellular and molecular biological characteristics from HPV-negative HNSCC. However, differences in circulating tumor cells (CTCs) between HPV-positive and -negative HNSCC remain unclear. Materials and methods: We first analyzed eight epithelial-mesenchymal transition (EMT)-related genes ( VIM, CDH1, CDH2, SNAI1, SNAI2, TWIST1, ZEB1, and ZEB2 ) using The Cancer Genome Atlas (TCGA) database. Next, we isolated CTCs from patients with HNSCC using CD45-negative selection and expression analysis of epithelial-related genes ( EPCAM, EGFR, and MET ) by RT-qPCR. CTC-positive samples were further analyzed for EMT-related genes. In addition, we investigated the proportion of circulating T cell subsets and CD38+ T cells using flow cytometry and their involvement in CTCs. Results: Compared with HPV-negative HNSCC, expression of CDH1, SNAI1, SNAI2, TWIST1, and ZEB1 was downregulated in HPV-positive HNSCC, as determined by TCGA analysis. CTCs were detected in 19 (52.8 %) of 36 HPV-positive and 26 (68.4 %) of 38 HPV-negative patients with HNSCC. EPCAM -positive and MET -positive CTCs were significantly more frequent in patients with HPV-negative HNSCC. HPV-positive patients with HNSCC exhibited significantly high SNAI1 and ZEB2 expression in CTCs. Interestingly, differences in SNAI1 expression levels differed markedly between CTCs and TCGA based on HPV status. Moreover, HPV-positive patients with HNSCC exhibiting SNAI1 -high CTCs showed a superior prognosis and a lower proportion of CD38+ T cells than those with SNAI1 -low CTCs. Conclusion: Our results provide novel insights into the EMT-MET spectrum of CTCs and may contribute to the development of prognostic biomarkers for HPV-positive HNSCC.